Seasonal and interannual variations in the distributions of tuna-associated dolphins in the eastern tropical Pacific Ocean - C. Fielder, Paul; Lennert-Cody, Cleridy E. (J. Cetacean Res. Manage., 2019)
Seasonal and interannual (El Niño–La Niña) variations in dolphin distributions in the eastern tropical Pacific Ocean have not been quantified, in spite of an extensive research vessel database. Fisheries observer data from the yellowfin tuna purse-seine fishery, collected year-round from 1986 through 2015, were used to construct a binned spatiotemporal dataset of the presence/absence of spotted, spinner and common dolphin schools by month and 1Â° area. Distribution patterns were predicted from generalised additive logistic regression models applied to the binned data, with dynamic predictors of surface temperature and salinity, thermocline depth and a stratification index. The dolphin taxa, especially common dolphins, show some niche separation in relation to these variables. Predicted distributions for each taxon showed seasonal and interannual differences. Spotted and spinner dolphins responded to changes in the position and size of the eastern Pacific warm pool and avoided the equatorial cold tongue in Septemberâ€“October and during La Niña. Common dolphins responded to seasonal and interannual changes in the Costa Rica Dome, the cold tongue, and the coastal upwelling habitat along Baja California, Peru and Ecuador. These predicted temporal variations are consistent with changes in preferred habitat driven by environmental variability.